Evaluation of Different Hybrid Distributed Generators in a Microgrid—A Metaheuristic Approach - Som, T.; Chakraborty, N. (Distributed Generation & Alternative Energy Journal, 2014)
An economic estimation of an autonomous power delivery system constituting different types of non-conventional and renewable energy resources has been performed considering an Indian load demand sce - nario. The mathematical analysis was done by the application of a modi- fied differential evolution (MDE). The MDE-evaluated total annual costs for the autonomous microgrid system utilizing three sets of distributed energy resources (DERs) have been compared. Solar module and fuel cells as DERs form the first set of DERs; solar module and bio-mass gas - ifier unit as DERs is considered as second set; and fuel cell along with Battery Energy Storage System (BESS) constitute the third set of DERs. Different types of consumers together form the microgrid with optimal supply of power from DERs. The optimal power generation conditions have been obtained pertaining to minimum cost of microgrid system. For the same load demand in microgrid operation, the results, using a hybrid solar-biomass system are found to be most cost effective. A re- duction of 6.9 % in the annual cost is obtained using the combination of solar module and biomass gasifier unit from that obtained using a solar module fuel cell combination. The corresponding reduction is 10% from that utilizing only fuel cell.